2022
DOI: 10.1155/2022/1747470
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of miR-146a-5p Promotes Acute Pancreatitis through Activating the TLR9/NLRP3 Signaling Pathway by Targeting TRAF6 In Vitro Rat Model

Abstract: Acute pancreatitis (AP) is mainly caused by acinar cells releasing various inflammatory factors, causing inflammatory storms and leading to severe pancreatitis. Detection methods and treatment targets for pancreatitis are lacking, raising the urgency of identifying diagnostic markers and therapeutic targets for AP. MicroRNAs (miRNAs) have recently been identified as molecular markers for various biological processes such as tumors, immunity, and metabolism, and the involvement of miRNAs in inflammatory respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…First, this finding is consistent with a previous study in which TRAF6 was found highly-expressed in both in vitro and in vivo AP and HTG-AP models, especially in HTG-AP groups [ 24 ]. Next, the TRAF6 gene was knocked down by siRNA-transfection in pancreatic acinar cells according to the most significant knockout efficiency in previous study [ 44 ]. On the other hand, three doses of MG-132 (from low to high) were administered in the in vivo AP model, and the optimum dose to reduce pancreatic injury was found to be 10 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…First, this finding is consistent with a previous study in which TRAF6 was found highly-expressed in both in vitro and in vivo AP and HTG-AP models, especially in HTG-AP groups [ 24 ]. Next, the TRAF6 gene was knocked down by siRNA-transfection in pancreatic acinar cells according to the most significant knockout efficiency in previous study [ 44 ]. On the other hand, three doses of MG-132 (from low to high) were administered in the in vivo AP model, and the optimum dose to reduce pancreatic injury was found to be 10 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…It also produces interleukin IL-1β and IL-18 that are released extracellularly to stimulate the inflammatory response, and pyroptotic cells further exacerbate the inflammation [12] . Activation of the nucleotide-binding domain, leucine-rich-containing family, pyrin domain-containing-3 (NLRP3) pathway is observed in other digestive disorders, such as acute pancreatitis, ulcerative colitis, and inflammatory bowel disease [13,14] . However, research on NLRP3 in GERD is limited.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%